The Effect of Cover Crop Management on Soil Conditions and Weed 6ontrol in a Colombar Vineyard in Oudtshoorn - Van Huyssteen, L.; Van Zyl, J.L.; Koen, A.P. (South African Journal of Enology and Viticulture, 2017)
Wimmera and vetch were used as vineyard cover crops in the hot and dry Klein Karoo region. The effect of different masses of dry cover crop residues used as mulches, as well as that of a growing crop, on soil moisture conservation was compared with the effect of a "bare soil" treatment. Data obtained comrrmed the common notion that in vineyards under dry-warm conditions any growing plants other than vines removed water from the soil which should have been available to the vines. Accumulative water consumption over the whole season on the mulched plots was 50 mm less than the total of 530 mm on plots with a growing cover crop. The mulch played an important role in moisture conservation, especially in the early and critical growth phase of the vines. The higher moisture content on the mulched plots was determined not only in the top layers, but also down to a depth of 120 cm. Under these climatic conditions a crop factor of0,50 for vineyards with growing cover crops is suggested. The implications of growing a cover crop in dry areas for organic matter production, weed control and moisture conservation are discussed. It was concluded that biological weed control by means of mulches, produced by growing cover crops in the vineyard, can replace pre-emergence herbicides.